Highly efficient phosphorescent materials based on Ir(iii) complexes-grafted on a polyhedral oligomeric silsesquioxane core. Issue 34 (8th August 2016) - Yu, Tianzhi; Xu, Zixuan; Su, Wenming; Zhao, Yuling; Zhang, Hui; Bao, Yanjun
Abstract : Three hybrid materials containing a POSS core were synthesized and characterized, in which two materials were used for light-emitting devices. Abstract : A new iridium(iii ) complex containing a coumarin derivative as the cyclometalated ligand (L) and a carbazole-functionalized β-diketonate (Cz-acac-allyl) as the ancillary ligand, namely, Ir(iii ) bis(3-(pyridin-2-yl)coumarinato- N, C 4 )(1-(9-butyl-9 H -carbazol-3-yl)hept-6-ene-1, 3-dionato- O, O ) [Ir(L)2 (Cz-acac-allyl)], was firstly synthesized as the emissive iridium(iii ) complex. Then three new phosphorescent polyhedral oligomeric silsesquioxane (POSS) materials, consisting of the emissive Ir(iii ) complex and carbazole moieties covalently attached to a polyhedral oligomeric silsesquioxane (POSS) core were successfully synthesized by hydrosilylation reaction in the presence of platinum(0)-1, 3-divinyl-1, 1, 3, 3-tetramethyldisiloxane (Pt-dvs) as the catalyst. These phosphorescent POSS materials offer many advantages including amorphous properties, good thermal stabilities, and good solubility in common solvents, and high purity via column chromatography. The photoluminescence spectra of the POSS materials in solution and in the solid state indicate a reduction in the degrees of interactions among the Ir(iii ) complex units and concentration quenching due to the bulky POSS core. Solution processed light-emitting devices based on these phosphorescent POSS materials exhibit a maximum external quantum efficiency (EQE) of 9.77%.